The Cambridge companion to John Wesley - Maddox, Randy L.; Vickers, Jason E. (Cambridge companions to religion, 2010)
Introduction / Randy L. Maddox & Jason E. Vickers -- Wesley's context -- The long eighteenth century / Jeremy Gregory -- Wesley's life -- Wesley's life and ministry / Kenneth J. Collibs -- Wesley in context / David N. Hempton -- Wesley's work -- Wesley as revivalist : renewal leader / Charles I. Wallace -- Wesley as reacher / William J. Abraham -- Wesley as biblical interpreter / Robert W. Wall -- Wesley as diarist and correspondent / Ted A. Campbell -- Wesley as editor and publisher / Isabel Rivers -- Wesley's engagement with the natural sciences / Randy L. Maddox -- Wesley as adviser on health and healing / Deborah Madden -- Wesley's theological emphases / Jason E. Vickers -- Wesley's emphases on ethics / Rebekah L. Miles -- Wesley's emphases on worship and the means of grace / Karen B. Westerfield Tucker -- Wesley's legacy -- Spread of Wesleyan Methodism / Kenneth Cracknell -- The Holiness, Pentecostal, Charismatic extension of the Wesleyan tradition / Randall J. Stephens -- The African-American wing of the Wesleyan tradition / Dennis C. Dickerson -- Current debates over Wesley's legacy among his progeny / Sarah H. Lancaster